Green to blue polarization compensated c-axis oriented multi-quantum wells by AlGaInN barrier layers - Dadgar, Armin; Groh, L.; Metzner, S.; Neugebauer, S.; Blaesing, J.; Hempel, T.; Bertram, Frank; Christen, Juergen; Krost, A.; Andreev, Z.; Witzigmann, Bernd (Applied Physics Letters, 2013)
We report on an over 50% reduction in polarization field strength in c-axis oriented InGaN multi-quantum wells (MQW) by applying quaternary AlGaInN barrier layers with better polarization matching to InGaN than GaN barriers. With the reduction in polarization fields, a strong blue-shift in photoluminescence is observed in agreement with theoretical expectation and simulations. By gracing incidence x-ray diffraction measurements, we demonstrate that partial relaxation already occurs for GaN/InGaN MQWs. As a consequence, the requirement of higher In-content layers for green light emission is in conflict with increasing strain leading to lattice relaxation. © 2013 American Institute of Physics.
CRIS-Team Scopus Importer:2021-06-11